(3CHcGQ GdCacGQs - (3CHh GdUdGM GdMdHjs
(3ChdgG (B:s
(3GdMeO ddg GdPi QSe ai UaMGJ GdeUfhYGJ HQGgjf GdOdGFd GdebGWYGJ CeG HYO CjgG GdWGdH GdCSQGQ GdNajGf Yf Yde (B[ (3YdeGA (B] (3GdGNjGQ GdeLJgO (B[(3Hf (B] (3ai GdcTa hGdCNHGQ s
(3BNQgG (B:s
(3hgPG BNQ eG Mce Hg hGQO GdhbJ MaXfi Gddg hEjGce ef Yed jhLH GdebJ ef JUfja gPG GdLRA GdKGfi s
(3HgG fXGe GdJYbjHIs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
(3eUOQ GbJfGA GdCUd (B:s
(3ef GdNRGfI GdedcjI HeOjfI GdQHGW (B(190) s
Keywords: (3GdcjejGA h GdWHjYjGJs